Kết quả nghiên cứu chế tạo thang alen chỉ thị các locus đa hình F13A01, D8S1179 và HPRTB ở người Việt - Lê, Thị Bích Trâm (2016)
F13A01, D8S1179 and HPRTB are STR loci which are widely used in human identification and paternity testing in the world. These loci have alleles which contains repeated units of 4pb in length. To determine exactly the genotype of the loci, it is necessary to construct a standard allelic ladder. An allelic ladder is created by combination of many different alleles based on which we can determine exactly genotype of each individual for a locus. In this communication, we describe a technique to construct allelic ladders for 3 STR loci: F13A01, D8S1179 and HPRTB using multigeneration amplification method. The first generation ladder is created by amplification using the template composed of different combined alleles. Then it can serve directly as a template source for production of the second and the third generation ladders. DNA template is diluted to three different concentration ratios in volume: 1/1000; 1/5000 and 1/10,000. Using this technique, allelic ladders of three generations were constructed. The ladders are of good quality and can be used to determine allel exactly in human identification and paternity testing.